Stanniocalcin 1 induction by thyroid hormone depends on thyroid hormone receptor β and phosphatidylinositol 3-kinase activation - Moeller, L C; Haselhorst, N E; Dumitrescu, A M; Cao, X; Seo, H; Refetoff, S; Mann, K; Janssen, O E (Experimental and clinical endocrinology & diabetes, 2011)
Thyroid hormone (TH) mediated changes in gene expression were thought to be primarily initiated by the nuclear TH receptor (TR) binding to a thyroid hormone response element in the promoter of target genes. A recently described extranuclear mechanism of TH action consists of the association of TH-liganded TRβ with phosphatidylinositol 3-kinase (PI3K) in the cytosol and subsequent activation of the PI3K pathway. The aim of this study was to examine the effect of TH, TRβ and PI3K on stanniocalcin 1 (STC1) expression in human cells. We treated human skin fibroblasts with triiodothyronine (T3) in the absence or presence of the PI3K inhibitor LY294002, a dominant negative PI3K subunit, Δp85α, and the protein synthesis inhibitor cycloheximide (CHX). The role of the TRβ was studied in cells from patients with resistance to thyroid hormone (RTH). STC-1 mRNA expression was measured by real-time PCR. We found an induction of STC1 by T3 in normal cells, but less in cells from subjects with RTH (2.7 ± 0.2 vs. 1.6 ± 0.04, P < 0.01). The effect of T3 was completely abrogated by blocking PI3K with LY294002 (3.9 ± 0.5 vs. 0.85 ± 0.5; P < 0.05) and greatly reduced after transfection of a dominant negative PI3K subunit, demonstrating dependency on the PI3K pathway. These results establish STC1 as a TH target gene in humans. Furthermore, we show that STC1 induction by TH depends on both TRβ and PI3K activation.